ANALYSIS OF BRAND PERSONALITY ON CUSTOMER LOYALTY (CASE STUDY TABLET COMPUTER: APPLE IPAD AND SAMSUNG GALAXY TAB) - Andu, Risca A. (FEB Universitas Sam Ratulangi Manado, 2013)
Brand personality is a potential marketing strategy to increase the customer loyalty towards the particular brand. Many customers will choose products with a brand that suitable with their personality. It also applies to tablet computer customers. The objectives of this research are to describe the effect of brand personality on customer loyalty in purchasing Apple Ipad and Samsung Galaxy Tab. This research also will analyze the difference in customer loyalty based on brand personality between Apple Ipad and Samsung Galaxy Tab. Theories supporting research are customer loyalty and brand personality. The method that used in this research is Simple Regression and Independent Sample t-test. Simple Regression is a method to determine whether the independent variable has significant effect on dependent variable. Independent Sample t-test is a method to compares the mean score of two groups on a given variable. There are three findings that can be the result of this research. First is brand personality significantly effect on customer loyalty in purchasing Apple Ipad. Second is brand personality significantly effect on customer loyalty in purchasing Samsung Galaxy Tab. Third is brand personality of Apple Ipad has higher customer loyalty than brand personality of Samsung Galaxy Tab. Keywords: customer loyalty, brand personality